PENGUKURAN STOK KARBON TERSIMPAN PADA HUTAN MANGROVE BUATAN DI AREA BEKAS TSUNAMI DI ACEH BARAT SELATAN - Wintah Wintah; Maiza Duana; Kiswanto Kiswanto (Journal of Aceh Aquatic Sciences, 2017)
Mangrove in the ex-Tsunami Area have ability to stored carbon, with existing of mangrove forest so increasing of carbon emission in natural can be diminished. Therefore, mangrove habitat is a big storage of carbon (carbon sinks). Carbon sinks or carbon dioxyde sinks have a important role as a place for storing or absorbing carbon dioxyde gases that derived from earth atmosphere. The carbon that absorbed by mangrove will stored in biomass of tree. The amount of such tree biomass will influenced carbon stock that stored in mangrove forest. The aim of this research is to known mangrove vegetation conditions to the ex-Tsunami in the West-South of Aceh Area. The research method that used is survey method. The sampling of mangrove vegetation that undertaken by using plot sampling method. The result showed the vegetation condition of mangrove forest in the ex-Tsunami Area were dominated by Rhizopora apiculata for seeds level. The pole level were dominated by Sonneratia alba. Carbon stock that stored in mangrove vegetation in the Ex-Tsunami Area is 36,03 tonnes/ha in the West-South of Aceh